EFFECTIVENESS OF THE IMPLEMENTATION OF HANDWORK DESINFECTION IN IMPROVING PREVENTION COMPLIANCE AND CONTROL OF CROSS INFECTION IN LAB. DENTAL AND MOUTH HEALTH SERVICES - Slamet Yadi Riyadi; Rina Kurnianti (Poltekkes Kemenkes Jambi, 2018)
Infectious diseases are still one of the health problems in the world, including Indonesia. Judging from the origin or acquisition of infection can come from the community (Community Acquired Infection) or come from the health service environment or clinic. Disinfectants can be interpreted as chemicals or physical influences that are used to prevent infection or contamination of microorganisms such as bacteria and viruses, as well as to kill or reduce the number of microorganisms or other germs. While antiseptics are defined as chemicals that can inhibit or kill the growth of microorganisms such as bacteria, fungi and others in living tissue. Disinfectant can be used for hand, floor, room, equipment and clothing disinfection. The purpose of this study was to determine the effectiveness of the application of disinfection hand washing in improving compliance with prevention and control of cross infection in the Lab. Dental and oral health care services. This research is a quantitative research with the method of quasy expriment approach, and data collection from primary data obtained from observation forms. The study population was all semester VI DIV Dental Nursing in 2018 totaling 24 people, the sample was taken by purposive sampling technique. The results of the research on hand washing disinfection showed that handwashing was more effective in increasing the prevention of cross infection in the laboratory of Dental and Oral Health Care Services Department of Dental Nursing at the Ministry of Health of the Ministry of Health of Jambi with a significance value of 0.000 (p <0.05). It is recommended for students to improve the compliance of disinfection hand washing for prevention and control of cross infection while working as a patient operator in dental and oral health laboratories.